Analisis Penerapan Fungsi Manajemen Dalam Sistem Administrasi Dan Pengadaan Di PT. PLN Indonesia Power-UBP KEPRI Melalui Skema Internship - Yurika Larasati; Siti Fatimah Alzahra; Siti Maheran Maheran; Nurfa Dhilah Nurdin (EMASHA: Jurnal Ekonomi, Manajemen dan Akuntansi Syariah, 2026)
This article presents an academic reflection of an internship program under the Merdeka Belajar Kampus Merdeka (MBKM) scheme conducted for three months (March–May 2026) at PT PLN Indonesia Power, Riau Islands Power Generation Business Unit (UBP Kepri). The internship focused on two crucial functions: Finance and General Administration, as well as Goods and Services Procurement. This study aims to analyze the application of management functions planning, organizing, actuating, and controlling in both units, as well as to examine the procurement mechanisms and their implications for the operational efficiency of a state-owned enterprise. Participatory observation, interviews, and document analysis were employed as research methods. The findings reveal that both financial administration and procurement functions at UBP Kepri operate in a structured manner guided by principles of transparency, accountability, and integrity, as reflected in the Anti-Bribery Management System (ABMS/SMAP) and the Integrity Due Diligence (IDD) instrument. This internship experience successfully integrated Islamic Business Management academic theory into real-world industrial practice, confirming the relevance of the MBKM program in preparing students for the professional world.